An Integrated Test-Based Nonlinear Aeroelastic Analysis Method to Freeplay-Induced Limit-Cycle Oscillations - Yukai Sun; Zhigang Wu; Chao Yang; Xiangyu Wang; Chuansheng Wang (International Journal of Aerospace Engineering)
The nonlinear limit-cycle oscillations induced by aileron rotational freeplay are investigated by numerical simulation and flutter wind tunnel tests. An integrated nonlinear aeroelastic analysis method and procedure based on the nonlinear system identification technology is proposed. Based on the characteristics of the structure, a low-speed nonlinear flutter wing-aileron model that considers both the linear flutter test and the nonlinear limit-cycle oscillation test with aileron rotational freeplay is designed. The wind tunnel tests are conducted with the model, and the stable limit-cycle oscillation is observed by accelerometers under the linear flutter boundary with a 0° angle of attack. Higher-order harmonic vibration is also observed with a low proportion compared to the fundamental oscillation, and the limit-cycle oscillation grows gradually with the increase of airspeed until flutter occurs. The comparison of numerical and experimental investigation shows high consistency.